Information technologies in knowledge economy - Đorđević Boljanović, Jelena; Vukašinović, Jelena; Veinović, Mladen (The European Journal of Applied Economics, 2014)
This paper analyses the importance of information and communication technologies in knowledge management and the impact on the increase of competitive advantage of organizations of their independent neighbouring countries. Comparative analysis has been conducted for the Republic of Serbia, Croatia and Bosnia and Herzegovina. The data of the World Economic Forum concerning the use of information technologies served as the baseline for this study. Moreover, the data from job advertisements announced by employers in these three countries during the period March-May 2013 have been experimentally analyzed. The results show that the application of information technologies is almost the same in all three countries, amounting to approximately 65%.